Factors influencing purchase intention: empirical study on brand Implora - Chandra, Yanto; Berlianto, Margaretha Pink (Institute of Computer Science (IOCS), 2024)
his study aims to investigate the factors that influence purchase intention for Implora brand products. Employing a quantitative approach, data were collected from a sample of consumers through structured questionnaires distributed online. The research model was constructed based on relevant literature, combines the factors of brand awareness, brand image, brand interactivity, content quality, online advertising, perceived value, trust, and purchase intention. Statistical analyses, including regression analysis and correlation coefficients, were employed to analyze the data. The results explored the influence of perceived value, and brand image on trust. This research also shows the positive and significant impact of content quality and brand interactivity on brand awareness. Online advertising influences brand image positively and significantly. The findings indicate that brand awareness, brand image, and trust have a significant impact on purchase intention for Implora brand products. The study provides valuable insights for marketers and managers to develop effective marketing strategies that can improve customer purchase intention